Impact of ischemia time on islet isolation success and posttransplantation outcomes: A retrospective study of 452 pancreas isolations. Issue 4 (19th October 2020) - Wassmer, Charles‐Henri; Perrier, Quentin; Combescure, Christophe; Pernin, Nadine; Parnaud, Géraldine; Cottet‐Dumoulin, David; Brioudes, Estelle; Bellofatto, Kevin; Lebreton, Fanny; Berishvili, Ekaterine; Lablanche, Sandrine; Kessler, Laurence; et al.
Abstract : Many variables impact islet isolation, including pancreas ischemia time. The ischemia time upper limit that should be respected to avoid a negative impact on the isolation outcome is not well defined. We have performed a retrospective analysis of all islet isolations in our center between 2008 and 2018. Total ischemia time, cold ischemia time, and organ removal time were analyzed. Isolation success was defined as an islet yield ≥200 000 IEQ. Of the 452 pancreases included, 288 (64%) were successfully isolated. Probability of isolation success showed a significant decrease after 8 hours of total ischemia time, 7 hours of cold ischemia time, and 80 minutes of organ removal time. Although we observed an impact of ischemia time on islet yield, a probability of isolation success of 50% was still present even when total ischemia time exceeds 12 hours. Posttransplantation clinical outcomes were assessed in 32 recipients and no significant difference was found regardless of ischemia time. These data indicate that although shorter ischemia times are associated with better islet isolation outcomes, total ischemia time >12 hours can provide excellent results in appropriately selected donors. Abstract : Prolonged total and cold pancreas ischemia times negatively impact islet isolation success, but not posttransplantation outcomes.